International transferability of immigrants’ human capital - Chiswick, B.; Miller, Paul (Pergamon, 2009)
This paper uses the approach in the under/over education literature to analyze the extent of matching of educational level to occupational attainment among adult native born and foreign born men in the US, using the 2000 Census. Overeducation is found to be more common among recent labor market entrants, while undereducation is more likely among older workers. Among immigrants, greater pre-immigration labor market experience is associated with poorer job matches, presumably due to the less-than-perfect international transferability of foreign experience. A longer duration in the US, however, is associated with a lower probability of being overeducated and a greater probability of being undereducated. This is consistent with immigrants being favorably selected for occupational advancement but this effect becomes realized only after overcoming the disadvantages of the less-than-perfect international transferability of their pre-immigration skills.